Comparison of Timed Blood Glucose Levels in Combination Injection Acceptors with Progesterone Injections in Midwife Independent Practices Clinic - Agustina Pribadi; Lisda Handayani; Siti Noor Hasanah; Novita Dewi Iswandari (MBUnivPress, 2024)
Injectable contraception is the most widely used because it is practical, cheap and safe. The use of depot medroxyprogesterone acetate injectable contraceptives or combination injections containing the hormone progesterone has the effect of increasing glucose levels. Long-term use will worsen the function of the pancreas in producing insulin and cause serious complications such as diabetes mellitus, nerve damage, heart disease, eye disease and kidney problems. Objective of this research is To know the picture of blood sugar levels when the acceptor injects a combination of injecting progesterone at the Independent Practice of Midwife. This type of quantitative analytical research was carried out in January 2024. The research sample was 41 people who injected the combination and 41 people who injected progesterone. Data collection with acceptor form. Research Result from the 82 acceptors, the maximum duration of use was ≤ 2 years, namely 50 people (60.98%). The highest parity was in multiparas, 54 people (65.8%), 74 people (90.24%) experienced weight gain. Only 2 people (2.4%) had abnormal blood sugar levels. Data were analyzed using the Wilcoxon test, showing that the average blood sugar level of acceptors who injected the combination was 104.02 gr/dl and progesterone injected 114.39 gr/dl. Shows that the average blood sugar level of acceptors who inject progesterone is higher than those who inject the combination with a p-value of 0.930 (p>0.05), indicating that there is no significant comparison between blood sugar levels when injecting the combination with injecting progesterone. The results of the study showed no significant difference between blood sugar levels during the 1 month injection and the 3 month injection. Considering the influence of progesterone in increasing blood sugar, midwives should check blood sugar values periodically so that blood sugar can be determined.